2009
DOI: 10.1161/circinterventions.109.886945
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up on a Large Cohort of “Full-Metal Jacket” Percutaneous Coronary Intervention Procedures

Abstract: Background-Limited long-term data exist on patients who have undergone drug-eluting stenting of very long lesions (requiring Ն60 mm of continuous stent) in native coronary arteries ("full-metal jacket"). Methods and Results-We examined consecutive procedures taking place between March 2002 and 2007 at 2 high-volume centers in Milan, Italy. Exclusion criteria were percutaneous coronary intervention for restenosis, percutaneous coronary intervention to a bypass graft, or percutaneous coronary intervention for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 25 publications
5
41
3
Order By: Relevance
“…Finally, the treated vessel can still be a potential, or in case of a CTO, a new goal for further surgical revascularization. Treating a CTO lesion with stents can result in a "full-metal jacket" procedure with well-known disadvantages [25,26]; these may be for the most part resolved owing to the advantages of BVS mentioned above. The mean number of scaffolds implanted in this study is comparable to the number of stents used in other current studies, whereas the mean scaffold length per patient is slightly higher in our registry despite the CTO length being lower [15,27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the treated vessel can still be a potential, or in case of a CTO, a new goal for further surgical revascularization. Treating a CTO lesion with stents can result in a "full-metal jacket" procedure with well-known disadvantages [25,26]; these may be for the most part resolved owing to the advantages of BVS mentioned above. The mean number of scaffolds implanted in this study is comparable to the number of stents used in other current studies, whereas the mean scaffold length per patient is slightly higher in our registry despite the CTO length being lower [15,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown acceptable short-and medium-term outcomes from the FMJ procedure [1][2][3][4][5][6]. However, long-term outcome data are limited, and there is controversy on the efficacy and safety of this approach [7].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-eluting stents (DES) subsequently proved to decrease the need for reintervention; consequently, they replaced bare metal stents (BMS) in percutaneous coronary intervention (PCI) for complex long lesions 2 . A few small registries have suggested that PCI using a full metal jacket (FMJ) with DES may be a safe procedure for the treatment of diffuse coronary lesions, with acceptable immediate and late clinical outcomes 3-6 . Other factors related to vessel diameter and lesion location are also reported to impact the rate of restenosis, including the use of vein grafts and the presence of ostial lesions and bifurcations 7 .…”
Section: Introductionmentioning
confidence: 99%